2023
DOI: 10.1039/d2tb02279f
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting carboxylic group functionalization of silica sol–gel materials

Abstract: The carboxylic chemical group is a ubiquitous moiety present in amino acids, a ligand for transition metals, a colloidal stabilizer, a weak acidic ion-exchanger in polymeric resins and given this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 193 publications
0
2
0
Order By: Relevance
“…Meanwhile, they can be easily linked or conjugated to the surface of UCNPs to facilitate functionalization. To facilitate linkage or surface conjugation, the surface of UCNPs is typically subject to further modifications, such as stripping ligand [ 98 ] and altering ligand molecules by introducing functional groups like carboxyl, [ 149 ] amino, [ 150 ] aldehyde, [ 151 ] thiol, [ 152 ] and more. Amino acids can serve dual roles as stabilizers and functionalizers of UCNPs.…”
Section: Ucnps Biosensorsmentioning
confidence: 99%
“…Meanwhile, they can be easily linked or conjugated to the surface of UCNPs to facilitate functionalization. To facilitate linkage or surface conjugation, the surface of UCNPs is typically subject to further modifications, such as stripping ligand [ 98 ] and altering ligand molecules by introducing functional groups like carboxyl, [ 149 ] amino, [ 150 ] aldehyde, [ 151 ] thiol, [ 152 ] and more. Amino acids can serve dual roles as stabilizers and functionalizers of UCNPs.…”
Section: Ucnps Biosensorsmentioning
confidence: 99%
“…Recent studies by Singh N. and Tkalec G. [ 8 , 18 ] have indicated that silica aerogels could be viable for drug delivery systems [ 19 , 20 ]. Researchers investigated the silica aerogels impregnated with the number of active pharmaceutical ingredients (API) by conducting adsorption experiments.…”
Section: Introductionmentioning
confidence: 99%